The dynamic of maturity stage of harumanis in greenhouse using growing degree day method - Noor Izzati Binti Mat Jenan (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Growing degree day is a web-based product that can provide decision support on a variety of issues throughout the entire growing season by integrating current conditions, historical climate data and projection of mango growing degree day through the end of the growing season. The purpose of this project is to determine the dynamic growth of fruit to full maturity, to evaluate the Harumanis growth for two periods in a difference starting month along a dry seasonat the beginning in November until February to analyze the correlation between growth and time by curve fitting of different GDD formulation in relation.The vernier caliper and temperature sensor were used in this project to obtain the diameter of Harumanis and the GDD values for two periods.The dynamic graph growth of Harumanis for two periods was evaluated until reach maturity stage at week 11 and week 12 respectively and it showed S pattern graph growth. The Harumanis growth started to reach the maturity stage in week 11 to week 12. The result from this research reported that a small difference from GDD values for Period 1 and Period 2 which are 1059.96GDD and 979.32 GDD respectively.The polynomial line of the graph in this research also reported that the value R2 for Period 1 is 0.9948 while R2 for Period 2 is 0.9961. Both of the periods showed the good of presenting data performance of GDD data. So, the Harumanis mango was predicted to reach the maturity stage at week 11 to week 12 in with the diameter around 84mm by the starting value of Harumanis diameter is 21.5(5.5)mm.